Nanoparticle proximity controls selectivity in benzaldehyde hydrogenation - Lim, Kang Rui Garrick; Kaiser, Selina K.; Wu, Haichao; Garg, Sadhya; Perxés Perich, Marta; van der Hoeven, Jessi E. S.; Aizenberg, Michael; Aizenberg, Joanna (Nature Catalysis, 2024)
Disentangling the effects of nanoparticle proximity and size on thermal catalytic performance is challenging with traditional synthetic methods. Here we adapt a modular raspberry-colloid-templating approach to tune the average interparticle distance of PdAu alloy nanoparticles, while preserving all other physicochemical characteristics, including nanoparticle size. By controlling the metal loading and placement of pre-formed nanoparticles within a 3D macroporous SiO2 support and using the hydrogenation of benzaldehyde to benzyl alcohol and toluene as the probe reaction, we report that increasing the interparticle distance (from 12 to 21 nm) substantially enhances selectivity towards benzyl alcohol (from 54% to 99%) without compromising catalytic performance. Combining electron tomography, kinetic evaluation and simulations, we show that interparticle distance modulates the local benzyl alcohol concentration profile between active sites, consequently affecting benzyl alcohol readsorption, which promotes hydrogenolysis to toluene. Our results illustrate the relevance of proximity effects as a mesoscale tool to control the adsorption of intermediates and, hence, catalytic performance.